Comparison of the Effects of Intratecal Morphine Administration and Transversus Abdominis Muscle Block as Post-Caesari Section Analgesics - Bambang Sulistyo (Pusat riset dan Inovasi Nasional, 2026)
The problem that is often faced by patients after cesarean section surgery is pain in the operating area, many therapies are used to reduce pain scores in patients. From non-medical mentosa, medical therapy to pain intervention. Two of the methods to reduce postoperative cesarean section pain are intrathecal morphine injections and transversus abdominis muscle blocks (TAP blocks). This study aims to find differences in pain scores after sectio caesaria surgery between patients who received intrathecal morphine and patients who received TAP block. An experimental study used the Post Test Only Control Group Design on Dirgahayu Hospital patients. A total of 108 patients were divided into 3 groups. Group K was not intervened by pain, group B was intervened by TAP block, group M was intervened with intrathecal morphine injection. VAS score was measured at the 4th hour postoperatively. Data were analyzed with the One-Way ANOVA test followed by the Post Hoc Test Bonferroni. Lower pain score was obtained in the group that received pain intervention than the control group with a significant difference (p<0.05). The pain scores of patients who received TAP block were lower than those who received intrathecal morphine with a significant difference (p<0.05). There was a significant difference in pain scores between intrathecal morphine and TAP block. It is hoped that TAP block administration will be used to reduce the pain scale after sectio caesaria surgery. Further research is needed regarding these 2 methods.